Mapping Global Research Trends And Thematic Evolution Of Plan–Do–Check–Act Studies Through Bibliometric Visualization - Andry Fitrian; Maryuni Kabul Budiono (International Journal of Management, Innovation, and Education, 2024)
This study aims to map global research trends and thematic evolution related to the PDCA (Plan–Do–Check–Act) framework from 2019 to 2024 using bibliometric visualization techniques. The PDCA cycle, initially proposed by W. Edwards Deming, remains a cornerstone of quality management and continuous improvement across diverse fields, including education, healthcare, manufacturing, and public administration. Employing a quantitative bibliometric approach, data were extracted from the Scopus database comprising 735 indexed documents within the specified period. The analysis was conducted using VOSviewer and R Studio (Biblioshiny) to identify publication trends, country collaborations, keyword co-occurrences, and citation networks. The results indicate a consistent increase in PDCA-related publications over the past five years, with dominant research clusters focusing on quality management systems, continuous improvement, lean manufacturing, and educational quality assurance. Thematic evolution analysis shows a shift from industrial quality control applications toward broader interdisciplinary implementations in sustainability and digital transformation contexts. The United States, Japan, and China emerged as the most productive contributors, while Indonesia shows growing engagement in educational and organizational development studies. This study concludes that PDCA research is evolving from procedural quality frameworks into adaptive models supporting innovation and learning in complex systems. The findings provide a comprehensive reference for future scholars to identify research gaps and strategic directions in PDCA-based quality improvement studies.